Paying for the view? How nursing home prices affect certified staffing ratios - Dörte Heger; Annika Herr; Anne Mensen (Health Economics, 2022)
Many countries limit public and private reimbursement for nursing care costs for social or financial reasons. Still, quality varies across nursing homes. We explore the causal link between case-mix adjusted nurse staffing ratios as an indicator of care quality and different price components in Swiss nursing homes. The Swiss reimbursement system limits and subsidizes the care price at the cantonal level, which implicitly limits staffing ratios, while the residents cover the nursing home-specific lodging price privately. To estimate causal effects, we exploit (i) the exogeneity of the Swiss care price regulation, (ii) nursing-home fixed effects estimations and (iii) instrumental variables for the lodging price. Our estimates show a positive impact of prices on certified staffing ratios. We find that a 10% increase in care prices increases certified staffing ratios by 3–4%. A comparable 10% increase in lodging prices raises certified staffing ratios by 1.5–10% (depending on the model). Our findings highlight that price limits for nursing care impose a limit on staffing ratios. Furthermore, our results indicate that providers circumvent price limits by increasing lodging prices that are privately covered. Thus, this cost shifting implicitly shifts the financial burden to the residents.
Keywords: 330; care quality; long-term care; nursing home; prices; staffing ratios